2004
DOI: 10.1007/s00204-004-0628-2
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of low doses of 14C-bisphenol A in male, female, pregnant, fetal, and neonatal rats

Abstract: Bisphenol A (BPA) is a weak xenestrogen (ADI = 50 microg kg(-1), US EPA) which is mass-produced, with potential for human exposure. To study absorption, distribution, excretion, and metabolism of BPA, BPA labeled with carbon-14 was administered p.o. to male and female Fischer (F344) rats at relatively low doses (20, 100, and 500 microg kg(-1)), and i.v. injected at 100 and 500 microg kg(-1). 14C-BPA (500 microg kg(-1)) was also administered orally to pregnant and lactating rats to examine the transfer of radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 19 publications
7
51
0
Order By: Relevance
“…Our study is also different from previous studies in the continuous exposure of the pups to BPA or mixtures during the lactation period. Digit ratios were found to be fixed exclusively by prenatal exposure, whereas AGD was modulated by the compounds both during gestation and postnatal exposure of the pups (the transmission to pups to the three compounds tested via milk has been demonstrated; ( [47,48], J. P. Cravedi 2005, unpublished data). In summary, digit ratios and AGDs in experimental studies involving continuous exposure to endocrine disruptors are different markers that may be jointly assessed for the detection of associations with other phenotypic changes.…”
Section: Discussionmentioning
confidence: 96%
“…Our study is also different from previous studies in the continuous exposure of the pups to BPA or mixtures during the lactation period. Digit ratios were found to be fixed exclusively by prenatal exposure, whereas AGD was modulated by the compounds both during gestation and postnatal exposure of the pups (the transmission to pups to the three compounds tested via milk has been demonstrated; ( [47,48], J. P. Cravedi 2005, unpublished data). In summary, digit ratios and AGDs in experimental studies involving continuous exposure to endocrine disruptors are different markers that may be jointly assessed for the detection of associations with other phenotypic changes.…”
Section: Discussionmentioning
confidence: 96%
“…Crain et al [7] reported that BPA at the environmentally relevant concentration of 21 mg/L or less can disrupt the endocrine system of many living organisms. Suzuki and Hattori [13] demonstrated that BPA can cause a decrease in the calcium level and calcitonin secretion in plasma of goldfish, suppressing the activities of tartrate-resistant acid phosphatase and alkaline phosphatase b. Kurebayashi et al [14] found trace disposition of BPA in adult, pregnant, and neonatal rats. Domoradzki et al [15] reported the pharmacokinetics and metabolism of BPA at three different stages of pregnancy in Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…Kurebayashi et al (2005) also reported that a small amount of radioactivity is transferred to the rat foetus, but only during late pregnancy (not before GD 18). No distinction could be made between free-or conjugated BPA, due to the low levels observed.…”
Section: In Utero Exposure and Kineticsmentioning
confidence: 94%
“…Considering that the BPA concentration in water in polycarbonate bottles was indicated to be as low as 0.33 ± 0.15 μg/L, this finding seems to be not fully consistent and limits the value of the described results. Kurebayashi et al (2005; cited in the 2006 EFSA opinion) reported the recovery of BPAderived radioactivity in neonatal tissues (mostly located in the intestinal content) from two pups 24 and 48 hr after oral administration of 14 C-BPA (500 μg/kg b.w.) to a single lactating rat on PND 11 (Kurebayashi et al, 2005).…”
Section: Neonatal Exposure and Kineticsmentioning
confidence: 99%
See 1 more Smart Citation